APPLICATION OF THE SCHRODINGER EQUATION TO A PARTICLE IN A ONE-DIMENSIONAL POTENTIAL WELL - Mukhtarov Erkin Kobilzhonovich (Galaxy International Interdisciplinary Research Journal, 2023)
It is impossible for students to master the basic ideas and conclusions of quantum mechanics without solving a certain set of problems. Problems play a significant role in the educational process, forming not only logical thinking, but also influencing the overall development of the students. The article poses and solves problems about stationary one-dimensional problems in quantum mechanics.